Parenting Program Management in Improving Student Morals - Noviyanti, Sinta; Wasliman, Iim (Journal of Innovation and Research in Primary Education, 2025)
Contemporary educational institutions face unprecedented challenges in fostering student moral development amid rapidly evolving technological and social environments. Parenting programs have emerged as strategic interventions for character development, yet limited research has systematically examined their management implementation within educational settings. This qualitative descriptive case study examined parenting program management in two vocational schools in West Java, Indonesia: SMKN 1 Cihampelas and SMK Wirakarya 2 Ciparay. Data were collected through semi-structured interviews with school administrators, teachers, counselors, and parents, complemented by non-participant observation and documentary analysis. Data analysis employed thematic analysis guided by George R. Terry's management functions framework: planning, organizing, actuating, and controlling. The findings revealed significant deficiencies across all management functions. Planning lacked systematic needs assessment and measurable indicators for moral development outcomes. Organizational structures demonstrated poor coordination between stakeholders with unclear responsibility divisions. Program implementation remained largely incidental and unsystematic, with low parent participation rates (30-40%). Supervision and evaluation mechanisms were absent, preventing measurement of program effectiveness in improving student morals. Both schools showed reactive rather than proactive approaches to parenting program management, limiting their potential impact on character development. These findings contradict established management principles and highlight critical gaps in educational practice. The study contributes empirical evidence demonstrating that program effectiveness depends on systematic management implementation rather than content design alone. The research provides a comprehensive framework for understanding how educational institutions can optimize parenting programs through proper management practices, offering practical implications for educational administrators and policy makers seeking to enhance moral development outcomes through school-family partnerships.